Protection Services' Efficacy in Controlling Violence against Children - Roes Peter Pomar (Journal La Sociale, 2021)
Child protection system is a planning, implementation, evaluation, and accountability unit. Since children are the nation's future generation, it is appropriate for a smart country to constantly attempt to safeguard its young generation from all possible dangers. A service van for women and children may help settle instances of child abuse. The Integrated Service Center for the Protection of Women and Children in Wajo Regency should devote more attention to child abuse via coaching, mentoring, and child protection. It is hoped that this will improve the safety of all children